KAJIAN KUALITAS, HIGIENE SANITASI DAN PENGAWASAN DEPOT AIR MINUM ISI ULANG (DAMIU) DI WILAYAH KERJA UPT PUSKESMAS SUNGAI PAKNING - Chairani Putri; Kesaktian Manurung; Henny Arwina Bangun; Donal Nababan; Mido Ester J Sitorus (HUMAN CARE JOURNAL, 2023)
Clean water is a basic human need. Based on data on the number of DAMIUs, there were 19 depots. Supervision was carried out, checking the quality of depot water both physically, chemically and microbiologically. From all DAMIUs it was found that the output quality of bacteriologically treated water and pH exceeded the threshold. This study aims to determine the quality of refill drinking water in the working area of the UPT Puskesmas Sungai Pakning Kec Bukit Batu in 2022. Qualitative research results of qualitative analysis to answer the quality of refill drinking water and see data on the results of water quality in the physical, chemical and microbiological laboratories as well as data from observations of depot sanitation hygiene through IKL and E-Monev applications with descriptive statistics to describe through measuring instruments and processed according to their functions. The results of the research are from the results of water quality analysis both physically, chemically and microbiologically at 19 DAMIU, 2 depots that have not met the requirements, namely for hardness and manganese and when viewed from environmental sanitation Hygiene inspections from April to June, even though the entire depot has met IKL requirements, there are several variables in the Hygiene questionnaire which are assumed to affect water quality such as inadequate equipment at some depots for example expired microfilters and suboptimal backwash systems which result in a decrease in water quality. From the results of supervision by officers through IKL-Emonev contamination through operators at work such as not washing hands before serving consumers. The lack of implementation of socialization activities and direct guidance by the relevant agencies for all operators and not understanding how to apply good sanitation hygiene in water treatment can result in physical, chemical and microbiological water quality in drinking water not meeting quality standards.